Liming and ion mobility in an Oxisol under surface application of flue dust, aqueous lime, sewage sludge and limestone - Corrêa, Juliano Corulli; Büll, Leonardo Theodoro; Crusciol, Carlos Alexandre Costa; Marcelino, Rafael; Mauad, Munir (Pesquisa Agropecuaria Brasileira, 2007)
The experiment was carried out under field conditions in a no-tillage system from 2002 to 2005, aiming to evaluate liming, base saturation and nitrate, calcium and magnesium mobility in a dystrophic Clay Rhodic Hapludox soil. The possible interference of organic acid catering of black oat through surface application of flue dust, aqueous lime and sewage sludge from a centrifuge and a biodigestor were also evaluated at rates of zero (control), 2, 4 and 8 t ha-1 as well as an additional treatment of dolomitic limestone at the rate of 2 t ha-1. Due to the increasing surface applications of flue dust, aqueous lime and sewage sludge from a centrifuge, soil pH value increased; these three residues and the sewage sludge from a biodigestor increased base saturation and availability of nitrate, calcium and magnesium up to the depth of 40 cm and within three months only. The low concentration of organic acid in the aerial part of the black oat did not explain the quicky nutrient leaching and soil acidity neutralization in depth. Flue dust, aqueous lime and sewage sludge from a centrifuge can be used as an acidity corrective and applied on the soil surface in no-tillage system.